2015
DOI: 10.1103/physrevc.91.024912
|View full text |Cite
|
Sign up to set email alerts
|

Charm quark energy loss in infinite QCD matter using a parton cascade model

Abstract: We utilize the Parton Cascade Model to study the evolution of charm quarks propagating through a thermal brick of QCD matter. We determine the energy loss and the transport coefficient 'q' for charm quarks. The calculations are done at a constant temperature of 350 MeV and the results are compared to analytical calculations of heavy quark energy loss in order to validate the applicability of using a Parton Cascade Model for the study of heavy quarks dynamics in hot and dense QCD matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 93 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…Therefore, the evolution of the HQs in the thermal bath of light quarks and gluons can be treated within the ambit of Brownian motion, although a detailed investigation of this problem within the framework of Boltzmann equation has revealed that the evolution of charm quarks as a Brownian particle requires some corrections [12] (see also [13,14,15,16,17,18]). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the evolution of the HQs in the thermal bath of light quarks and gluons can be treated within the ambit of Brownian motion, although a detailed investigation of this problem within the framework of Boltzmann equation has revealed that the evolution of charm quarks as a Brownian particle requires some corrections [12] (see also [13,14,15,16,17,18]). …”
Section: Introductionmentioning
confidence: 99%
“…Heavy flavor as a probe of the medium has generated significant interest in the recent past due to the suppression of its momentum distribution at large momentum in the thermal medium, denoted by R AA ðp T Þ [2][3][4][5] and its elliptic flow (v 2 ) [4]. Several attempts have been made to study these factors within the framework of the Fokker-Plank equation [1,[6][7][8][9][10][11][12][13][14][15][16][17][18] and Boltzmann equation [19][20][21][22]. However, the roles of hadronic phase have been ignored in these works.…”
Section: Introductionmentioning
confidence: 99%
“…The last appears within the data error bars to be more close to the possibility to predict simultaneously both R AA and v 2 for Pb + Pb at √ s = 2.76 ATeV. Also other authors have in the past and more recently undertaken the study of charm quarks within a Boltzmann approach [40,41,42,43].…”
Section: Boltzmann Vs Fokker-planck Dynamicsmentioning
confidence: 84%